Growth Performance and Physiological Variables for Broiler Chickens Subjected to Short-Term Elevated Carbon Dioxide Concentrations - Olanrewaju, H.A.; Dozier, W.A.; Purswell, J.L.; Branton, S.L.; Miles, D.M.; Lott, B.D.; Pescatore, A.J.; Thaxton, J.P. (International Journal of Poultry Science, 2008)
Four trials were conducted to evaluate growth responses, blood chemistry and heart characteristics of broiler chicks subjected to progressive concentrations (0, 3,000, 6,000, 9,000 ppm) of carbon dioxide (CO2) gas from 1-14 days of age, which were then discontinued throughout the remainder of the trial (42 days of age). On days 14 and 42 of each trial, 20 birds per chamber were randomly selected for immediate analysis of blood partial pressure of CO2 (pCO2), blood partial pressure of O2 (pO2), blood pH, hematocrit (Hct), hemoglobin (Hb), blood electrolytes (Na+, K+, Ca2+ and Cl-) and determination of heart characteristics. Body and feed weights were recorded at 0, 14, 28 and 42 days of age for growth performances. Final body weight (BW) gain and feed conversion were similar among the treatments, but cumulative mortality significantly increased as CO2 increased (P ≤ 0.05) from 3,000-9,000 ppm. Treatments did not alter blood pCO2 and pO2 concentrations at age 14 and 42 days of age. Increasing CO2 up to 9,000 ppm failed to reveal differences for heart weight characteristics at 14 days of age, but total heart and left ventricle weights were increased at 42 days of age. These results indicate that subjecting chicks to progressive concentrations of CO2 from 1-14 days of age does not adversely alter blood chemistry or cumulative growth performance, but increased the incidence of late-mortality.